Hydrogenation of CIS-1-4-poly(isoprene) nad natural rubber catalyzed by OsHCI(CO)(O2(PCY3)2 and [Ir(COD)py(PCY3)]PF6 - Kitikorn Charmondusit (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2001